Responsabilidad ante la «solución final». Acerca del Informe Arendt sobre el caso Eichmann - Campos Zamora, Francisco J. (2013)
The prosecution against Adolf EICHMANN, charged with crimes against the Jewish people, began in Jerusalem on April 11th 1961. Hannah ARENDT, sent by The New Yorker to cover that process, published her coverage in her later work “EICHMANN in Jerusalem: A Report on the Banality of Evil”. ARENDT’s interpretation on this process calls for polemics; while she describes EICHMANN as a plain, even banal, individual, she also reproaches the collaboration of the Jewish councils during the Holocaust. This article reviews the highlights of the process as well as the conclusions that ARENDT drew from EICHMANN, the notion of banality of evil, and the concepts of guilt and responsibility.